2008
DOI: 10.1161/hypertensionaha.108.114322
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Angiotensin-Converting Enzyme 2 Overexpression in Vessels of SHRSP Rats Reduces Blood Pressure and Improves Endothelial Function

Abstract: Abstract-Rat models of hypertension, eg, spontaneously hypertensive stroke-prone rats (SHRSP), display reduced angiotensin-converting enzyme 2 (ACE2) mRNA and protein expression compared with control animals. The aim of this study was to investigate the role of ACE2 in the pathogenesis of hypertension in these models. Therefore, we generated transgenic rats on a SHRSP genetic background expressing the human ACE2 in vascular smooth muscle cells by the use of the SM22 promoter, called SHRSP-ACE2. In these transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 50 publications
10
124
1
4
Order By: Relevance
“…Recently, the role of ACE2 in the modulation of cardiovascular function has been investigated by deliberate genetic manipulation, including targeted disruption (5,6) and overexpression (7)(8)(9), and these studies have consistently demonstrated that ACE2 has beneficial effects of antihypertension, antifibrosis and antiatherosclerosis. Thus, ACE2 may provide a new therapeutic target for the treatment of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of ACE2 in the modulation of cardiovascular function has been investigated by deliberate genetic manipulation, including targeted disruption (5,6) and overexpression (7)(8)(9), and these studies have consistently demonstrated that ACE2 has beneficial effects of antihypertension, antifibrosis and antiatherosclerosis. Thus, ACE2 may provide a new therapeutic target for the treatment of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that enhanced ANG II/AT 1 signaling in the aortas of HFD-fed rats might be responsible for the downregulation of ANG-(1-7)/MAS/ACE2 axis and NO bioavailability. Overexpression of ACE2 or chronic ANG-(1-7) infusion has been shown to reduce blood pressure, and this effect may be due to the degrading of local ANG II and the improving of endothelial dysfunction (46,47). Previously, HS has been shown to suppress ANG II-induced hypertension in aorta (23).…”
Section: Discussionmentioning
confidence: 99%
“…7 In another line of ACE2 knockout mice, BP was significantly increased following Ang II infusions, 47 in sharp contrast to the spontaneous hypotension observed in ACE knockout mice, 48 suggesting that, in addition to the Ang II system, ACE2 might regulate BP through other peptide systems, such as bradykinin and/or Apelin. Nevertheless, exogenous supplementation of ACE2 by gene transfer decreased BP in SHR hypertensive rats, 38 and recombinant ACE2 treatment attenuated Ang II-induced hypertension specifically. 49 Thus, ACE2 clearly must function as a negative regulator of the RAS in BP control.…”
Section: Ace2 As a Negative Regulator Of The Ras In The Cardiovasculamentioning
confidence: 93%
“…Those hypertensive rats show reduced ACE2 transcripts and protein expression in both heart and kidney. 7 Transgenic ACE2 overexpression in the vessels of SHRSP rats reduces blood pressure (BP) and improves endothelial function, 38 and neuronal overexpression of ACE2 also attenuates hypertension. 39, 40 In humans, several studies have shown a strong association of ACE2 polymorphisms to hypertension in female Chinese patients with metabolic syndrome, 41 essential hypertension 42-45 or diabetes-associated hypertension.…”
Section: Ace2 As a Negative Regulator Of The Ras In The Cardiovasculamentioning
confidence: 99%